2014
DOI: 10.1136/gutjnl-2014-306998
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-mediated signalling attenuates inflammatory responses in experimental colitis

Abstract: ObjectiveEosinophils reside in the colonic mucosa and increase significantly during disease. Although a number of studies have suggested that eosinophils contribute to the pathogenesis of GI inflammation, the expanding scope of eosinophil-mediated activities indicate that they also regulate local immune responses and modulate tissue inflammation. We sought to define the impact of eosinophils that respond to acute phases of colitis in mice.DesignAcute colitis was induced in mice by administration of dextran sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 59 publications
9
87
1
1
Order By: Relevance
“…10S,17S-DiHDoHE, 17R-RvD1 and RvD5 belong to SPM [26, 34] and 14S-HDoHE is a precursor to maresin 1, another SPM [35]. Although we did not observe significant change in IL-6 and TNF-α production from RAW264.7 cells after these SPM treatment for 12 hrs, 14S-HDoHE, 7R-RvD1 and RvD5 showed their anti-inflammatory function in LPS-stimulated BM macrophages.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…10S,17S-DiHDoHE, 17R-RvD1 and RvD5 belong to SPM [26, 34] and 14S-HDoHE is a precursor to maresin 1, another SPM [35]. Although we did not observe significant change in IL-6 and TNF-α production from RAW264.7 cells after these SPM treatment for 12 hrs, 14S-HDoHE, 7R-RvD1 and RvD5 showed their anti-inflammatory function in LPS-stimulated BM macrophages.…”
Section: Discussioncontrasting
confidence: 49%
“…3C). It has been acknowledgeable that 14, 15-EET [23], 5, 6-EET [24], 5, 6-DHET [25], 10S,17S-DiHDoHE[26], 17R-RvD1 [27], RvD5 [27] and PGE 1 [28] are anti-inflammatory while 12-HETE is pro-inflammatory [29]. Together these results showed that cupping treatment increased anti-inflammatory lipids and decreased pro-inflammatory lipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, eosinophil levels positively correlate with disease severity in these patients 148 . Additionally, deficiency in MBP 149 , eotaxin-1 24 or eosinophils themselves 150 protects against experimental murine models of colitis, although not in all cases 151 . Eosinophils also have important roles in the remodeling and fibrosis that occur in ulcerative colitis, as eosinophil depleted mice have protection from spontaneous ileitis and tissue remodeling 152 .…”
Section: Roles Of Eosinophils In the Pathogenesis Of Mucosal Inflammamentioning
confidence: 99%
“…Secondly, recent studies have shown that eosinophils in lamina propria are able to induce the differentiation of regulatory T (Treg) cells by producing TGF-β1 and all-trans retinoic acid (ATRA) [46]. Moreover, in mouse models of acute peritonitis or acute colitis, eosinophil-deficient mice developed significantly more severe inflammation than wild-type mice, which suggests that eosinophils play protective roles in terminating acute inflammation, possibly due to their production of the anti-inflammatory lipids such as protectin D1 (PD1) [47,48].…”
Section: Protecting the Immune Homeostasis: Roles In Bone Marrow Gutmentioning
confidence: 99%